Inflation Targeting in Georgia : Are We There Yet? - Bakradze, Giorgi; Billmeier, Andreas (Washington, D.C. : International Monetary Fund, 2007)
This paper evaluates whether Georgia is ready to adopt inflation targeting (IT), a monetary policy framework that several emerging markets have adopted recently. After reviewing selected prerequisites for successfully implementing IT, the paper focuses on whether one specific precondition is in place-an empirically stable monetary transmission mechanism. Building on a baseline VAR model, it presents several extensions to explore the various channels using causality tests, impulse responses, and variance decompositions. The paper finds that once the central bank overcomes some institutional and operational weaknesses and establishes a more reliable transmission mechanism, it could adopt IT over the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet